Applicability of virtopsy in veterinary practice: a short review - Ibrahim, Abdulazeez Okene; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2012)
Virtopsy is a new and rapidly evolving non-invasive autopsy procedure involving the use of modern imagingmodalities. It basically consists of three-dimensional body surface scanning by photogrammetry, multi-slicecomputed tomography (MSCT) and magnetic resonance imaging (MRI) for analysis and recording of autopsylesions to ascertain cause and manner of death. This technique has been shown to be as effective and accurateas a conventional autopsy in the recent forensic studies. The MSCT is the most frequently used image modalityfor fractures, pathological gas formation and trauma, while the MRI is a good tool for soft tissue pathology. Itis hoped that virtopsy will replace or serve as an indispensable adjunct to conventional autopsies in the future.Nonetheless, there is currently a paucity of information on the use of virtopsy in veterinary necropsy practicein which it could be used as a research tool and also possibly replace common procedures. The term 'virtopsy'in this article refers to the use of high throughput imaging techniques in human or animals as it may warrant.This review would look at the history, applications, prospects and limitations of virtopsy in veterinary necropsy.